تقرير عن الحالة الاجتماعية في العالم ١٩٩٧ - United Nations (United Nations, 1997)
The Report offers new insights into the nature and magnitude of the pressing social problems and the national and international policies required to address them. It examines the core social issues of poverty alleviation, productive employment and social integration covering concepts and quantitative indicators, as well as policies and strategies.